Effectiveness of mobile health interventions to improve nasal corticosteroid adherence in allergic rhinitis: A systematic review. Issue 9 (16th November 2021) - Baxter, Mats Stage; Tibble, Holly; Bush, Andrew; Sheikh, Aziz; Schwarze, Jürgen
Abstract: Background: Mobile health interventions (MHI) offer the potential to help improve nasal corticosteroid (NCS) adherence in allergic rhinitis (AR). The aim of this systematic review was to summarise the current evidence on the effectiveness of MHI for improving NCS adherence in AR. Methods: We systematically searched MEDLINE, Embase and the Cochrane Central register of Controlled Trials (CENTRAL) for randomised controlled trials filtered for publication dates between 2010 and 2021. We evaluated the effects of MHI aiming to improve NCS adherence on self‐management outcomes in AR and comorbid conditions. Two reviewers independently screened potential studies, extracted study characteristics and outcomes from eligible papers and assessed risk of bias using the Cochrane Risk of Bias tool 2.0. High heterogeneity precluded meta‐analysis. Data were descriptively and narratively synthesised. Results: Our searches identified 776 individual studies of which 4 met the inclusion criteria. These studies were heterogeneous with respect to participant, intervention and outcome characteristics. We considered all outcome‐specific overall risk of bias assessments to be of high risk of bias except for two studies examining NCS adherence which received 'some concern' grades. The three studies which reported on NCS adherence found that MHI were associated with improvement in NCS adherence. Significant MHI‐associated improvement in symptoms or disease‐specific quality of life was found in one study each, whilst no study reported significant differences in nasal patency. Conclusions: Whilst MHI showed potential to improve NCS adherence, their effect on clinical outcomes varied. Furthermore, robust studies with longer intervention durations are needed to adequately assess effects of MHI and their individual features on NCS adherence and clinical outcomes.